Clinical hematology atlas - Carr, Jacqueline H. (Saunders Elsevier, 2009)
Ideal for identifying cells at the microscope, this atlas covers the basics of hematologic morphology, including examination of the peripheral blood smear, basic maturation of the blood cell lines, and discussions of a variety of clinical disorders. Over 400 photographs, schematic diagrams, and electron micrographs illustrate hematology from normal cell maturation to the development of various pathologies.